2010
DOI: 10.1021/ed100422c
|View full text |Cite
|
Sign up to set email alerts
|

Using Item Response Theory To Assess Changes in Student Performance Based on Changes in Question Wording

Abstract: Five years of longitudinal data for general chemistry student assessments at the University of Georgia have been analyzed using item response theory (IRT). Our analysis indicates that minor changes in question wording on exams can make significant differences in student performance on assessment questions. This analysis encompasses data from over 6100 students, giving an extremely small statistical uncertainty. IRT provided us with a new insight into student performance on our assessments that is also importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…As for the distractors, Answer Choice 1 (only gravity acts) is attractive to students at the very lowest end of the total score range (<2). Answer Choice 3 (gravity and a force in the direction of motion act) preferentially attracts students at the low end of the range as well (2)(3)(4)(5)(6)(7)(8)(9)(10). The IRC for Answer Choice 5 (gravity, a force in the direction of motion, and a force pointing from the center of the circle outward) shows a broad peak in the range of total scores of 9-16, while the IRC for Answer Choice 4 (gravity, a force exerted by the channel toward the center of the circle, and a force in the direction of motion) shows a broad peak in the total score range of 14-23.…”
Section: Additional Fci Insights From Irc Analysismentioning
confidence: 99%
“…As for the distractors, Answer Choice 1 (only gravity acts) is attractive to students at the very lowest end of the total score range (<2). Answer Choice 3 (gravity and a force in the direction of motion act) preferentially attracts students at the low end of the range as well (2)(3)(4)(5)(6)(7)(8)(9)(10). The IRC for Answer Choice 5 (gravity, a force in the direction of motion, and a force pointing from the center of the circle outward) shows a broad peak in the range of total scores of 9-16, while the IRC for Answer Choice 4 (gravity, a force exerted by the channel toward the center of the circle, and a force in the direction of motion) shows a broad peak in the total score range of 14-23.…”
Section: Additional Fci Insights From Irc Analysismentioning
confidence: 99%
“…[21] It has been shown that specific phrasing of questions and options is an important aspect. [22][23][24] Questions seemingly unambiguous to experts were understood differently, but still in a reasonable manner, by novices. [22] On the other hand, it is an (often implicit) objective of many courses that students are able to handle the terminology, models, and underlying assumptions.…”
Section: The Challenge Of Multiple-choice Question Developmentmentioning
confidence: 97%
“…Instead, the responses may be a parroting back of the stem of the question. In fact, studies in the sciences have shown that even small alterations in context and question wording influence the content of student responses to constructed-response questions (Nehm, & Ha, 2011;Schurmeier, Atwood, Shepler, & Lautenschlager, 2010;Weston, Haudek, Prevost, Merrill, & Urban-Lurain, 2015).…”
Section: Constructed Response Itemsmentioning
confidence: 99%